2019
DOI: 10.3389/fmars.2019.00121
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Exposure to Heat and Sediment Triggers Changes in Coral Gene Expression and Photo-Physiological Performance

Abstract: Corals, together with their endosymbiotic Symbiodiniaceae, are known to exhibit a suite of mechanisms for survival under stressful conditions. However, exactly how the host animal responds to varying environmental conditions remains unclear. In this study, we tested two relevant environmental factors that can have deleterious effects on corals: heat and sediment. We examined among-genotype responses of Pocillopora acuta to these factors with RNA-Seq in concert with widely-used tools for assessing the physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 101 publications
(121 reference statements)
5
27
0
Order By: Relevance
“…During a more recent coral bleaching events in Singapore, the coral genus Pocillopora appeared to show a shift to being less susceptible [12,35], similar to observationsfrom the Great Barrier Reef, Australia [36,37]. While this genus is known to be highly plastic [24,38,39], the mechanisms underlying its enhanced resistance to and ability to recover from thermal stress remain unclear. Therefore, it is of interest to explore both photophysiological and transcriptional plasticity in Pocillopora, using Pocillopora acuta as the model species.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…During a more recent coral bleaching events in Singapore, the coral genus Pocillopora appeared to show a shift to being less susceptible [12,35], similar to observationsfrom the Great Barrier Reef, Australia [36,37]. While this genus is known to be highly plastic [24,38,39], the mechanisms underlying its enhanced resistance to and ability to recover from thermal stress remain unclear. Therefore, it is of interest to explore both photophysiological and transcriptional plasticity in Pocillopora, using Pocillopora acuta as the model species.…”
Section: Introductionsupporting
confidence: 61%
“…The selected genes of interest (GOIs) and internal control genes (ICGs) were derived from an RNA-Seq experiment conducted on P. acuta following heat exposure [38] as being the most responsive and stable, respectively. The transcript sequences used for primer designs were validated to be associated with corals only as reported in Poquita-Du et al [38]. The full list of candidate genes is shown in Table 1.…”
Section: Primer Design and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest relative levels of host hsp70 were recorded in near‐coast and reef samples collected in summer 2016. Results are in line with laboratory and field studies that reported increases in hsp expression following high heat‐light stress (reviewed in Louis et al., 2017; Poquita‐Du et al., 2019; Traylor‐Knowles et al., 2017; Zhang et al., 2018).…”
Section: Discussionsupporting
confidence: 88%
“…Also a well-studied 'lab rat' for experimental work in the Indo-Pacific (e.g. Ben-Haim et al 2003;Cumbo et al 2013;Poquita-Du et al 2019a), many P. damicornis-like colonies have been confirmed to be P. acuta at multiple localities, including Japan (Kitano et al 2015), Philippines (Torres and Ravago-Gotanco 2018), Singapore (Poquita-Du et al 2017), American Sāmoa (Montgomery et al 2019), Austral and Cook Islands (Mayfield et al 2015), and Hawai'i (Johnston et al 2018). These discoveries have wide-ranging impacts, even for the evaluation of species conservation status (see Agapow et al 2004;Mace 2004;Ely et al 2017).…”
Section: Introductionmentioning
confidence: 99%